The Effect Of Return On Assets And Price Earning Ratio Toward Stock Prices - Sinaga, Berliana; Hasanuh, Nanu (STIE PGRI Dewantara Jombang, 2020)
This study aims to determine the effect of Return on Assets (ROA) and Price Earning Ratio (PER) on stock prices. The population in this study was the construction and building sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2019 period. Through the purposive sampling method then obtained a sample of 7 companies and obtained 42 data. The data analysis technique used multiple linear regression and hypothesis testing. The results showed that partially Return On Asset has no significant effect on stock prices.